Potentially inappropriate medications in older Chinese outpatients based on the Beers criteria and Chinese criteria - Zhang, Ying; Chen, Zhaoyan; Tian, Fangyuan (Frontiers in Pharmacology, 2022)
Objective: Polypharmacy increases the prevalence of potentially inappropriate drugs (PIMs) among older persons, lowering their quality of life. This study aimed to compare the prevalence of PIMs in older Chinese outpatients according to the Beers criteria and the Chinese criteria and to analyze the risk factors. Second, we describe the differences between the two criteria, focusing on the inappropriate prescription of drugs in older outpatients. Methods: In Chengdu, Southwest China, a retrospective study was undertaken using electronic medical data from 9 medical institutions. Outpatients above the age of 60 who were treated in the Geriatrics Center of these medical institutions were included. The Beers criteria and the Chinese criteria were used to evaluate the PIM status of older outpatients, and logistic regression was used to identify potential risk factors for PIMs. Results: There were 44,458 prescriptions from 2016 to 2018. The prevalence of PIMs among older outpatients was 30.05% (according to the Beers criteria) and 35.38% (according to the Chinese criteria). Estazolam, hydrochlorothiazide and alprazolam were the top three PIMs in the Beers criteria, while the top three PIMs in the Chinese criteria were clopidogrel, estazolam and insulin. The prevalence of PIMs was associated with age, the number of diseases and the number of drugs. PIMs were shown to be more common in patients aged 70 and above, with more than 2 kinds of diseases and more than 4 kinds of drugs. Conclusion: PIMs were shown to be common among older outpatients in China, according to this study. The detection rate of the Chinese criteria was higher than that of the Beers criteria.